Cutaneous leishmaniasis and iron metabolism: current insights and challenges - Assouab, Aicha; Kihel, Ayyoub; Rouahi, Myriam; Larribau, Mathilde; Karim, Zoubida; Akarid, Khadija (Frontiers in Immunology, 2024)
Leishmaniasis is a vector-borne parasitic infection induced by protozoa of the genus Leishmania. The disease spectrum ranges from skin lesions to visceral leishmaniasis, which is fatal if untreated. The cutaneous leishmaniasis is characterized by a clinical polymorphism of lesions with a broad range of severity ranging from a self-limited lesion to multiple disfiguring lesions stigmatizing the patient for life. Although iron is required for several process of Leishmania infection including survival, growth and virulence, the number of studies on host iron metabolism during this infection remains limited. Iron homeostasis in the body is finely regulated by hepcidin, a hyposideremic peptide highly expressed in the liver. In infectious contexts, hepcidin plays additionally an antimicrobial role, acting through various mechanisms such as retaining iron in tissues, modulating the immune response, and operating as a defensin against gram-negative bacteria. This review mainly summarizes the most important interconnections between iron metabolism, hepcidin and leishmaniasis. A deeper understanding of iron metabolism in this context could help in developing innovative treatment strategies that target the parasite while simultaneously reinforcing host defenses.